2019
DOI: 10.1177/1526602819887382
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Outcomes of Local Anesthesia and Peripheral Nerve Block for Hybrid Lower Extremity Revascularization

Abstract: Purpose: To investigate the utilization of local anesthesia or peripheral nerve block with monitored anesthesia care (LPMAC) and its impact on the perioperative outcomes of hybrid lower extremity revascularization (LER) compared with general anesthesia (GA). Materials and Methods: A search of the ACS-NSQIP database between 2005 and 2017 identified 9430 patients who underwent hybrid LER for peripheral artery disease. Excluding 449 ineligible cases left 8981 hybrid LER patients for analysis. The patients were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…In terms of secondary outcomes, no association between regional technique and outcomes was found except for decreased non-home discharge and increased LOS; however, the differences were small, and these exploratory results should be interpreted with caution in the context of small sample size and multiple testing 25 . The difference in LOS may be related to the sicker population in the RA group, and the small magnitude of difference aligns with previous literature of small to no differences in LOS 19 , 20 , 24 . While RA was associated with decreased odds of non-home discharge, this may be related to the more complex grafts and surgeries in the GA group, though the mechanism remains to be elucidated given the lack of difference amongst rates of patency, reintervention, morbidity, and mortality outcomes in the current cohort.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In terms of secondary outcomes, no association between regional technique and outcomes was found except for decreased non-home discharge and increased LOS; however, the differences were small, and these exploratory results should be interpreted with caution in the context of small sample size and multiple testing 25 . The difference in LOS may be related to the sicker population in the RA group, and the small magnitude of difference aligns with previous literature of small to no differences in LOS 19 , 20 , 24 . While RA was associated with decreased odds of non-home discharge, this may be related to the more complex grafts and surgeries in the GA group, though the mechanism remains to be elucidated given the lack of difference amongst rates of patency, reintervention, morbidity, and mortality outcomes in the current cohort.…”
Section: Discussionsupporting
confidence: 88%
“…The literature has shown mixed results regarding the superiority of RA over GA for morbidity and mortality 1 , 5 , 19 , 20 , 24 . In terms of secondary outcomes, no association between regional technique and outcomes was found except for decreased non-home discharge and increased LOS; however, the differences were small, and these exploratory results should be interpreted with caution in the context of small sample size and multiple testing 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found varying results related to the impact of PNBs on major complications, but most were in orthopedic and vascular surgery patients. [29][30][31] We were unable to analyze whether PNBs enhance total mastectomy patients' quality of recovery because of a lack of data in NSQIP. Previous studies suggest that PNBs have a significant positive impact on quality of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature shows that there is a lack of objective data regarding the length of stay in the intensive care unit (ICU) of patients treated with hybrid revascularization for chronic limb-threatening ischemia and multilevel atherosclerotic lesions compared to the classical method of surgical revascularization [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%